Retinal Vascular Degeneration in the Transgenic P23H Rat Model of Retinitis Pigmentosa - Fernández-Sánchez, Laura; Esquiva, Gema; Pinilla, Isabel; Lax, Pedro; Cuenca, Nicolás (Frontiers in Neuroanatomy, 2018)
Retinitis pigmentosa (RP) is a group of inherited retinal degenerative diseases involving a progressive degeneration of photoreceptor cells. Following the loss of photoreceptors, retinal vascularization tends to decrease, which seems to play a role in the degenerative process of retinal cells. This study reports changes in retinal vascular network architecture in the P23H rat model of RP at different stages of retinal degeneration. Homozygous P23H line-3 rats of ages ranging from 18 days to 16 months were used in this study. Age-matched Sprague-Dawley (SD) rats were used as control animals. Vertical sections and wholemount retinas were immunolabeled for type IV collagen or stained using NADPH diaphorase histochemistry, and retinal vascular networks were drawn using a camera lucida. The superficial and deep capillary plexus (DCP) were fully developed at P18 in P23H rat retinas and showed no differences from the control animals. In 4-month-old P23H rat retinas, the superficial and intermediate capillary plexus were similar to those observed in age-matched SD rats, but a reduction in the DCP could be observed in these animals, with a significant decrease in both capillary density and capillary loops. At 16 months, the DCP was completely lost, and only vessels exhibiting an abnormal, tortuous dead-end could be observed. The middle capillary plexus had virtually disappeared at this age. Only perpendicular vessels connecting the superficial and DCP were found. The superficial plexus showed no changes in the vascular surface with age. In RP, photoreceptor loss is accompanied by degenerative changes in the retinal vascular network. The disruption of the capillary plexus, with loss of capillary density and capillary loops, can hamper the normal supply of oxygen and nutrients to retinal cells, thus accelerating retinal degeneration. Therefore, changes in retinal vascularization must be taken into account in the design of therapies targeting retinal degenerative diseases.